Multiwavelength Fiber Laser based on Bidirectional Lyot Filter in Conjunction with Intensity Dependent Loss Mechanism - A. H. Sulaiman; N. Md. Yusoff; N. A. Cholan; M. A. Mahdi (Institute of Advanced Engineering and Science, 2018)
We experimentally demonstrate a multiwavelength fiber laser (MWFL) based on bidirectional Lyot filter. A semiconductor optical amplifier (SOA) is used as the gain medium, while its combination with polarization controllers (PCs) and polarization beam combiner (PBC) induces intensity dependent loss (IDL) mechanism. The IDL mechanism acts as an intensity equalizer to flatten the multiwavelength spectrum, which can be obtained at a certain polarization state. Using different ratio of optical splitter has affected to multiwavelength flatness degradation. Subsequently, when we removed a polarizer in the setup, the extinction ratio (ER) is decreased. Ultimately, with two segments of polarization maintaining fiber (PMF), two channel spacings can be achieved due to splicing shift of 0° and 90°.